The Ksar Ghilane 002 shergottite—The 100th registered Martian meteorite fragment. (25th February 2013) - Llorca, Jordi; Roszjar, Julia; Cartwright, Julia A.; Bischoff, Addi; Ott, Ulrich; Pack, Andreas; Merchel, Silke; Rugel, Georg; Fimiani, Leticia; Ludwig, Peter; Casado, José V.; Allepuz, David
Abstract We report on the discovery of a new shergottite from Tunisia, Ksar Ghilane (KG) 002. This single stone, weighing 538 g, is a coarse‐grained basaltic shergottite, mainly composed of maskelynitized plagioclase (approximately 52 vol%) and pyroxene (approximately 37 vol%). It also contains Fe‐rich olivine (approximately 4.5 vol%), large Ca‐phosphates, including both merrillites and Cl‐apatites (approximately 3.4 vol%), minor amounts of silica or SiO2‐normative K‐rich glass, pyrrhotite, Ti‐magnetite, ilmenite, and accessory baddeleyite. The largest crystals of pyroxene and plagioclase reach sizes of approximately 4 to 5 mm. Pyroxenes (Fs26–96En5–50Wo2–41). They typically range from cores of about Fs29En41Wo30 to rims of about Fs68En14Wo17. Maskelynite is Ab41–49An39–58Or1–7 in composition, but some can be as anorthitic as An93. Olivine (Fa91–96) occurs mainly within symplectitic intergrowths, in paragenesis with ilmenite, or at neighboring areas of symplectites. KG 002 is heavily shocked (S5) as indicated by mosaic extinction of pyroxenes, maskelynitized plagioclase, the occurrence of localized shock melt glass pockets, and low radiogenic He concentration. Oxygen isotopes confirm that it is a normal member of the SNC suite. KG 002 is slightly depleted in LREE and shows a positive Eu anomaly, providing evidence for complex magma genesis and mantle processes on Mars. Noble gases with a composition thought to be characteristic for Martian interior is a dominant component. Measurements of 10Be, 26Al, and 53Mn and comparison with Monte Carlo calculations of production rates indicate that KG 002 has been exposed to cosmic rays most likely as a single meteoroid body of 35–65 cm radius. KG 002 strongly resembles Los Angeles and NWA 2800 basaltic shergottites in element composition, petrography, and mineral chemistry, suggesting a possible launch‐pairing. The similar CRE ages of KG 002 and Los Angeles may suggest an ejection event at approximately 3.0 Ma.